KOMUNIKASI DATA VIA KOMPUTER - warno, Warno (STIE YPPI Rembang, 2008)
Computers became indispensable in the development of information and communication, computer media and ad- vances in communications technology has an effect on the development of data processing. The majority of computer users is available at companies or offices, and a large com- pany often have branch offices. With so required data may be transferred from one branch to another branch with tele- communications equipment, which encourage the function- ing of a computer to generate information that truly reliable and fixed time. In broad outline of a circulation system con- sisting of data processing from data collection, processing, and distribution. For the data using a computer, data trans- mission using an electronic transmission system, usually referred to as data communication. In response to this, the need for skilled workers and who have knowledge of data communications is required. This paper will describe the tech- nical workings of how data communications using a com- puter. Components required for data communication and other forms of data communication itselfKey word: Communication, computer